Gut Microbiota Approach—A New Strategy to Treat Parkinson’s Disease - Liu, Jing; Xu, Fei; Nie, Zhiyan; Shao, Lei (Frontiers in Cellular and Infection Microbiology, 2020)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by neuronal loss and dysfunction of dopaminergic neurons located in the substantia nigra, which contain a variety of misfolded α-synuclein (α-syn). Medications that increase or substitute for dopamine can be used for the treatment of PD. Recently, numerous studies have shown gut microbiota plays a crucial role in regulating and maintaining multiple aspects of host physiology including host metabolism and neurodevelopment. In this review article, the role of gut microbiota in the etiological mechanism of PD will be reviewed. Furthermore, we discussed current pharmaceutical medicine-based methods to prevent and treat PD, followed by describing specific strains that affect the host brain function through the gut-brain axis. We explained in detail how gut microbiota directly produces neurotransmitters or regulate the host biosynthesis of neurotransmitters. The neurotransmitters secreted by the intestinal lumen bacteria may induce epithelial cells to release molecules that, in turn, can regulate neural signaling in the enteric nervous system and subsequently control brain function and behavior through the brain-gut axis. Finally, we proved that the microbial regulation of the host neuronal system. Endogenous α-syn can be transmitted long distance and bidirectional between ENS and brain through the circulatory system which gives us a new option that the possibility of altering the community of gut microbiota in completely new medication option for treating PD.